Sex-Related Differences in Outcomes According to Surgical Treatment Approach in Degenerative Mitral Regurgitation - Jérémy Bernard, PhD; Solenn Dal Soglio, MD; Bin Zhang, MD; Erwan Salaun, MD, PhD; Jonathan Beaudoin, MD; Éric Charbonneau, MD; Éric Dumont, MD; Dimitri Kalavrouziotis, MD; Siamak Mohammadi, MD; Philippe Pibarot, DVM, PhD; François Dagenais, MD; Marie-Annick Clavel, DVM, PhD (JACC: Advances)
Background: Sex differences in degenerative mitral regurgitation (DMR) are poorly described, especially according to surgical treatment approach (ie, mitral valve repair [MVr] vs replacement [MVR]). Objectives: We aimed to assess sex differences in presentation, treatment, and outcomes of patients surgically treated for DMR and identify sex-specific predictors of mortality. Methods: Consecutive patients treated by MVr or MVR between 2002 and 2019 were included (n = 1,804), and all data were prospectively collected. To account for confounders between men and women, the inverse probability weighting method was used in total population and within each treatment approach singly. The study endpoints were short-term postoperative (ie, ≤30 days) outcomes and long-term mortality. Results: Preoperatively, women (n = 661; 37%) presented more atrial fibrillation, higher values of brain natriuretic peptides, higher indexed values of left atrial and ventricular dimensions, and pulmonary pressure and were more symptomatic (all P ≤ 0.006). After inverse probability weighting, women were at higher risk of early stroke. They presented higher long-term mortality than men after MVr (HR: 1.62 [95% CI: 1.14-2.30], P = 0.007), whereas mortality was similar between sexes after MVR (HR: 0.91 [95% CI: 0.71-1.17], P = 0.47). Independent predictors of long-term mortality were mainly the presence of mitral annulus calcification in men, and left ventricular ejection fraction and DMR severity in women (all P ≤ 0.04). Conclusions: In this large series of patients surgically treated for DMR, women had worse preoperative presentation, higher early postoperative rates of stroke, and higher long-term risk of mortality when treated by MVr.